2020
DOI: 10.1111/phn.12819
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between housing instability and intimate partner violence: A retrospective study

Abstract: Objective: To examine the relationship between housing instability (HI) and intimate partner violence (IPV) over time, controlling for individual, situational, and social structural factors among women and to determine whether race/ethnicity modifies these relationships. Design and Sample: The study was a retrospective secondary data analysis from the Fragile Families and Child Well-Being Study. The sample included women who reported their housing status at year 5, yielding 4,000 women. Measures: Housing insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This finding contradicts other research trends that find that exposure to violence generally reduces with age [61]. Finally, women living in poverty were found to be at increased risk for intimate partner violence, which is consistent with previous research [5,[62][63][64][65][66]. Known to many, poverty contributes to stress and increases the possibility of violent explosive encounters in relationships [67].…”
Section: Discussionsupporting
confidence: 68%
“…This finding contradicts other research trends that find that exposure to violence generally reduces with age [61]. Finally, women living in poverty were found to be at increased risk for intimate partner violence, which is consistent with previous research [5,[62][63][64][65][66]. Known to many, poverty contributes to stress and increases the possibility of violent explosive encounters in relationships [67].…”
Section: Discussionsupporting
confidence: 68%
“…Syndemic theory posits that conditions, such as structural, social, and individual-level factors, are mutually reinforcing and interact leading to adverse health outcomes (see Figure 1) [16,17]. Previous studies found that housing insecurity, such as a lack of access, affordability, and homelessness were related to IPV [18][19][20], substance use [16,21,22], and factors that increased one's risk of acquiring HIV [23][24][25][26]. There is a dearth of research that has explored housing among BLCW through a syndemics lens.…”
Section: Syndemic Modelmentioning
confidence: 99%